Resilience of Rural Communities Facing Global Challenges - Yusriadi, Yusriadi; Andi Kaslin (Cendekiawan Indonesia Timur, 2025)
Rural communities globally face interconnected challenges, from climate change and natural disasters to economic shocks and pandemics, increasing their vulnerability. Effective adaptation and resilience strategies are crucial. This systematic review identifies, analyzes, and synthesizes these strategies employed by rural communities facing global challenges. Following PRISMA guidelines, the review will search Scopus, Web of Science, AGRICOLA, and JSTOR for peer-reviewed English articles (2010-2024). Keywords include